Water Quality - Tutu, Hlanganani (IntechOpen, 2017)
As concerns increase over the scarcity of water resources and the role of anthropogenic activities, water quality is evermore important. Activities ranging from agriculture to mining have had a bearing on the quality of water that they impact. Several studies assessing such impacts have been conducted at local and global scales over the years. This book, consisting of contributions by authors in various water-related fields, delves into some approaches that are used to understand and/or to improve water quality, and these include assessment of water chemistry, biomonitoring, modelling and water treatment. This book will be useful to environmental scientists, water professionals, researchers, academics and students.